Elite team sport athletes` perceptions and experiences of destructive coach leadership behavior - Sigvartsen, K. K.; Sæther, S. A.; Haugen, T.; Erikstad, M. K.; Peters, D. M.; Høigaard, R. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Research on coach leadership in sport has traditionally been aimed at positive aspects of coach leadership styles and behavior. Ineffective coach leadership has primarily been linked to the absence of constructive leader behavior, often labeled in the concept of laissez-faire leadership resulting in unsatisfactory performance and losses for both athletes and teams. Less research has focused on identifying behaviors that the coaches shouldn`t do; destructive behaviors that may undermine the immediate and long-term effect of their otherwise effective and constructive behaviors. The purpose of this study therefore was to explore elite team sport athletes` perceptions and experiences of destructive coach leadership behavior.